Sosialisasi Dan Penyuluhan Tentang Bahaya Narkoba Dan Pencegahannya Di Sekolah Yayasan Perguruan Pahlawan Nasional Medan - Cece Harahap; Agus Setiono; Desy Irana Dewi Lubis (Jurnal Pengabdian Masyarakat Akademisi, 2022)
The purpose of this activity is socialization, counseling and providing understanding about the dangers of drugs for the surrounding community is very important to do because then the community can have the same knowledge and understanding, namely about drug abuse and trafficking is not allowed and is strictly prohibited to do because it can lead to a problems and very large negative effects in social life. Therefore, there needs to be a synergy between stakeholders so that social problems of drug abuse can be overcome together. Socialization must be done early on. so we started from school. School is a place to get education and knowledge as well as a place to hang out, if the relationship is wrong it can lead to negative things, one of which is drugs. The National Heroes Junior High School was chosen to be the target of counseling on the grounds that teenagers at this level need to be educated because their period is a transitional period and they want to know everything. All students know the dangers of drugs, and some students know the types of drugs and how to use them. The information they know is obtained from social media.